Marriage and a socio-philosophical analysis of the problems leading to divorce in Uzbekistan. - Holmirzaev Hayitboy Dedahonovich, Yusupova Eleonora Ferdinandovna (International Journal of Advanced Science and Technology, 2020)
Just as there were different, even conflicting views on the existence of the universe in human evolution, there was another mythological and theological view of the origin of marriage and family relationships, which played an important role in human life.